Numerical taxonomic studies of the East African highland bananas (Musa AAA - East Africa) in Uganda - Karamura, D.A.; International Network for the Improvement of Banana and Plantain (1999)
The purpose of this study was to determine the variation pattern that exists in the East African Highland bananas (Musa AAA) grown in Uganda, estimate levels of dissimilarity caused by different growing conditions, and establish a flexible provisional classification and identification system. Techniques of numerical taxonomy were employed to determine the variation pattern. Sixty-one morphological characters were employed to determine differences among the 238 accessions available for the study. The East African Highland bananas have been kept as a subgroup within a group (Musa AAA). The smallest distinguishable units in the subgroup are clones and they have been grouped into clone sets. Five clone sets were delineated, based mainly on qualitative characters. The clone sets were distinct enough for new accessions to be fitted into them. These data can now be used to develop hypotheses concerning the evolutionary background of the East African Highland bananas and to exploit vigour, pest and disease resistance in the representative clones of the different clone sets proposed.